Corporate Response Against COVID-19: Manufacturing Shift by Ford-Otosan - Anil Yasin Ar; Asad Abbas (Ubiquity Press, 2021)
In the time of disasters and crisis, governmental organizations are responsible for performing disaster-relief tasks and providing economic support. However, these organizations may fail to fulfill their duties in emerging and developing market settings either because of a lack of resources or bureaucratic inefficiencies. At the rise of these situations, corporations are expected to help society via corporate social responsibility (CSR) projects. This viewpoint article reflects upon the Ford-Otosan's attempt to devise a CSR project to support Turkish citizens during the COVID-19 crisis and meet the public's expectations. This study aims to set a future research agenda on CSR and multinational joint-ventures' non-market strategies by illustrating a unique insight into an international joint-venture during the COVID-19 crisis.